EFFECT OF AGE, GENDER AND DURATION OF DIABETES MELLITUS ON THYROID DYSFUNCTION IN PATIENTS OF DIABETIC - Ali, Kamran; Shah, Sajid Ali; Ali, Syed Murtaza; Akbar, Raja Jibran; Raza, Syed Qasim; Kadir, Sadia (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the effect of age, gender and duration of diabetes mellitus on thyroid dysfunction in patients of diabeticStudy Design: Comparative cross sectional study.Place and Duration of Study: Medicine department, Combined Military Hospital, Peshawar, from Oct 2015 to Oct 2017.Methodology: The study was conducted after taking permission from hospital ethical review committee. Information was entered in the proforma, which included demographic information like age in years, gender, duration of disease and type of diabetes mellitus (DM) type. Already diagnosed patients with diabetes mellitus were included in the study. Thyroid function tests were carried out by standard laboratory procedure.Results: A total of 179 patients were included in our study, 114 (63.7%) were female and 65 (36.3%) were male. Mean body mass index in our study was 29.85 ± 3.88 kg/m2. Out of 179 patients 46 (25.7%) had thyroid dysfunction (TD). Out of the 46 patients with thyroid dysfunction, 14 patients (7.8%) had clinical hypothyroidism, while subclinical hypothyroidism was seen in 25 patients (14%). Clinical hyperthyroidism was reported in 3 (1.7%), while subclinical hyperthyroidism in 4 (2.2%) patients respectively.Conclusion: Age of patients, gender and duration of disease affect thyroid functions in patients with diabetes mellitus. Thyroid profile should be carried out in diabetic patients whose blood sugar level is difficult to control.